Evaluating the TUITEK® patient support program in supporting caregivers of children diagnosed with growth hormone deficiency in Argentina - Assefi, Aria Reza; Graham, Selina; Crespo, María Lourdes; Debicki, Matías; Reston, Jonathan; Gonzalez, Judit; Jheeta, Amrit; Koledova, Ekaterina (Frontiers in Endocrinology, 2023)
Introduction The appropriate use of recombinant human growth hormone (r-hGH) treatment provides an opportunity to improve growth outcomes among pediatric patients with growth hormone deficiency (GHD). However, a major challenge in clinical practice is to adequately recognize and address factors that negatively affect treatment adherence. TUITEK® patient support program (PSP) was designed to help caregivers of children diagnosed with GHD to personalize the care pathway, improve adherence, and achieve better outcomes. Effectiveness of TUITEK® PSP has been demonstrated previously in a smaller sample (n = 31) in Taiwanese population. Here, we present the results from Argentina. Methods TUITEK® PSP was piloted among 76 caregivers of children with GHD administering r-hGH using easypod™ (Merck KGaA, Darmstadt, Germany) auto-injector device in Argentina. Based on TUITEK® personalization questionnaire, caregivers were assigned to high- and low-risk groups across four categories that may influence adherence, including disease and treatment coherence (DTC), self-administration (SA), treatment-related anxiety (TRA), and emotional burden (EB). The caregivers who were included in atleast one high-risk group had the provision of telephone calls with a nurse practitioner every 2 weeks for 3 months. The Wilcoxon signed-rank test was employed to assess changes in questionnaire-based scoring patterns between baseline and follow-up evaluations. Results Statistically significant changes (p < 0.05) in questionnaire scores between baseline and follow-up evaluations were observed across the four categories. The mean/median DTC (n = 11) and SA (n = 23) scores changed from 2.45/3 and 2.17/2, respectively, to 4/4, with all the caregivers moving to low-risk group following program completion (100%) for both categories. The mean/median TRA score (n = 40) changed from 3.58/3 to 2.5/2 and 67.5% of patients (27/40) moved to low-risk group. The mean/median EB score (n = 32) changed from 3.69/3 to 3.13/3 however, none of the caregivers moved to low-risk group (0%). Conclusion TUITEK® PSP is a simple, practical, and time-efficient interventional tool that can be used to address key adherence-related issues among caregivers of children with GHD and provide personalized adherence support. Our findings demonstrate that TUITEK® PSP has the potential to improve treatment adherence and self-management, thereby improving growth outcomes in Argentina.